Leaf mineral nutrient remobilization during leaf senescence and modulation by nutrient deficiency - Maillard, Anne; Diquélou, Sylvain; Billard, Vincent; Laîné, Philippe; Garnica, Maria; Prudent, Marion; Garcia-Mina, José-Maria; Yvin, Jean-Claude; Ourry, Alain (Frontiers in Plant Science, 2015)
Higher plants have to cope with fluctuating mineral resource availability. However strategies such as stimulation of root growth, increased transporter activities, and nutrient storage and remobilization have been mostly studied for only a few macronutrients. Leaves of cultivated crops (Zea mays, Brassica napus, Pisum sativum, Triticum aestivum, Hordeum vulgare) and tree species (Quercus robur, Populus nigra, Alnus glutinosa) grown under field conditions were harvested regularly during their life span and analysed to evaluate the net mobilization of 13 nutrients during leaf senescence. While N was remobilized in all plant species with different efficiencies ranging from 40% (maize) to 90% (wheat), other macronutrients (K-P-S-Mg) were mobilized in most species. Ca and Mn, usually considered as having low phloem mobility were remobilized from leaves in wheat and barley. Leaf content of Cu-Mo-Ni-B-Fe-Zn decreased in some species, as a result of remobilization. Overall, wheat, barley and oak appeared to be the most efficient at remobilization while poplar and maize were the least efficient. Further experiments were performed with rapeseed plants subjected to individual nutrient deficiencies. Compared to field conditions, remobilization from leaves was similar (N-S-Cu) or increased by nutrient deficiency (K-P-Mg) while nutrient deficiency had no effect on Mo-Zn-B-Ca-Mn, which seemed to be non-mobile during leaf senescence under field conditions. However, Ca and Mn were largely mobilized from roots (-97 and -86% of their initial root contents, respectively) to shoots. Differences in remobilization between species and between nutrients are then discussed in relation to a range of putative mechanisms.